Migrating from user fees to social health insurance: exploring the prospects and challenges for hospital management - Atinga, R.A.; Mensah, S.A.; Asenso-Boadi, F.; Andoh Adjei, Francis-Xavier (BioMed Central, 2012)
Background: In 2003 Ghana introduced a social health insurance scheme which resulted in the separation of purchasing of health services by the health insurance authority on the one hand and the provision of health services by hospitals at the other side of the spectrum. This separation has a lot of implications for managing accredited hospitals. This paper examines whether decoupling purchasing and service provision translate into opportunities or challenges in the management of accredited hospitals. Methods: A qualitative exploratory study of 15 accredited district hospitals were selected from five of Ghana’s ten administrative regions for the study. A semi-structured interview guide was designed to solicit information from key informants, Health Service Administrators, Pharmacists, Accountants and Scheme Managers of the hospitals studied. Data was analysed thematically. Results: The results showed that under the health insurance scheme, hospitals are better-off in terms of cash flow and adequate stock levels of drugs. Adequate stock of non-drugs under the scheme was reportedly intermittent. The major challenges confronting the hospitals were identified as weak purchasing power due to low tariffs, non computerisation of claims processing, unpredictable payment pattern, poor gate-keeping systems, lack of logistics and other new and emerging challenges relating to moral hazards and the use of false identity cards under pretence for medical care. Conclusion: Study’s findings have a lot of policy implications for proper management of hospitals. The findings suggest rationalisation of the current tariff structure, the application of contract based payment system to inject efficiency into hospitals management and piloting facility based vetting systems to offset vetting loads of the insurance authority. Proper gate-keeping mechanisms are also needed to curtail the phenomenon of moral hazard and false documentation.
Keywords: Health insurance; user fee; hospital; management; reimbursement; claims management